The Role of Guidance and Counseling Programs in Enhancing Interpersonal Communication Skills on Elementary School Students: Implementation, Impact and Challenges - Fiptar Abdi Alam; Agus Akhmadi (Bulletin of Counseling and Psychotherapy, 2026)
Interpersonal communication skills are essential for students' social and emotional development, particularly in elementary education. This study examined the role of family dynamics in enhancing the outcomes of Guidance and Counseling programs in fostering these skills. The research employed a library-based methodology, analyzing peer-reviewed articles, books, and reports to synthesize insights into the interplay between home and school environments using Prisma Method. The findings indicated that positive family dynamics, characterized by open communication and emotional support, significantly reinforce students’ ability to apply communication strategies learned in school-based guidance programs. Conversely, families with conflict-ridden or rigid structures hinder the effectiveness of these interventions. Parental involvement, such as modeling empathetic listening and reinforcing respectful dialogue, was identified as a key factor in amplifying program outcomes. However, challenges such as limited parental engagement and misaligned expectations between families and schools remain prevalent. The study underscores the critical role of family-school collaboration in fostering consistent support for students’ interpersonal development. Recommendations include implementing parental education programs, establishing regular communication channels between teachers and parents, and addressing cultural barriers to engagement. Future research should explore the long-term effects of family involvement and assess the potential of digital tools to enhance collaboration, thus making interpersonal communication easier to understand between students, teachers and the school community.